(untitled) (Bangladesh Journal of Zoology, 2015)
The pattern of butterfly abundance, their diversity with abiotic (temperature, humidity, rainfall, photoperiod) and biotic (plants) factors were studied in the Butterfly Research Park (BRP) at Bhawal National Park, Gazipur, Bangladesh. Total 2393 individuals per day comprising 44 species under 32 genera belonging to the families Danaidae, Nymphalidae, Pieridae, Papilionidae, Lycaenidae, Hesperiidae and Satyridae were recorded from January to December, 2012. The butterflies were more abundant in the months of May, November, December; and least abundant in August and September respectively. Danaidae showed a highest abundance over the other families. Hesperiidae and Pieridae were very common; Nymphalidae and Papilionidae were common; and Lycaenidae and Satyridae were few in number respectively. Papilionids, Pierids and Nymphalids were found highest in May and June. Danaids, Satyrids and Hesperiids were peak in November and Lycaenids in April. Danaids and Papilionids were lowest in August; Hesperiids and Satyrids in March; Nymphalids, Pierids and Lycaenids were in September, October and December respectively. Bangladesh J. Zool. 41(2): 247-255, 2013